Penning trap mass measurements on nobelium isotopes - Dworschak, Michael Gerhard; Block, M.; Ackermann, D.; Audi, G.; Blaum, Klaus; Droese, C.; Eliseev, Sergey; Fleckenstein, T.; Haettner, E.; Herfurth, F.; Heßberger, F. P.; Hofmann, S.; et al. (Physical review. C, Nuclear physics, 2010)
The Penning trap mass spectrometer SHIPTRAP at GSI Darmstadt allows accurate mass measurements of radionuclides, produced in fusion-evaporation reactions and separated by the velocity filter SHIP from the primary beam. Recently, the masses of the three nobelium isotopes 252−254No were determined. These are the first direct mass measurements of transuranium elements, which provide new anchor points in this region. The heavy nuclides were produced in cold-fusion reactions by irradiating a PbS target with a 48Ca beam, resulting in production rates of the nuclei of interest of about one atom per second. In combination with data from decay spectroscopy our results are used to perform a new atomic-mass evaluation in this region.
Gesehen am 20.02.2023